Acceleration of osteogenic differentiation by sustained release of BMP2 in PLLA/graphene oxide nanofibrous scaffold. (8th September 2020) - Abazari, Mohammad Foad; Nasiri, Navid; Nejati, Fatemeh; Kohandani, Mina; Hajati‐Birgani, Nazanin; Sadeghi, Solmaz; Piri, Peyman; Soleimanifar, Fatemeh; Rezaei‐Tavirani, Mostafa; Mansouri, Vahid
Abstract : After about three decades of experience, tissue engineering has become one of the most important approaches in reconstructive medical research to treat non‐self‐healing bone injuries and lesions. Herein, nanofibrous composite scaffolds fabricated by electrospinning, which containing of poly(L‐lactic acid) (PLLA), graphene oxide (GO), and bone morphogenetic protein 2 (BMP2) for bone tissue engineering applications. After structural evaluations, adipose tissue derived mesenchymal stem cells (AT‐MSCs) were applied to monitor scaffold's biological behavior and osteoinductivity properties. All fabricated scaffolds had nanofibrous structure with interconnected pores, bead free, and well mechanical properties. But the best biological behavior including cell attachment, protein adsorption, and support cells proliferation was detected by PLLA‐GO‐BMP2 nanofibrous scaffold compared to the PLLA and PLLA‐GO. Moreover, detected ALP activity, calcium content and expression level of bone‐related gene markers in AT‐MSCs grown on PLLA‐GO‐BMP2 nanofibrous scaffold was also significantly promoted in compression with the cells grown on other scaffolds. In fact, the simultaneous presence of two factors, GO and BMP2, in the PLLA nanofibrous scaffold structure has a synergistic effect and therefore has a promising potential for tissue engineering applications in the repair of bone lesions.